1996
DOI: 10.1002/art.1780390716
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of plasma and urine complement split products as indicators of lupus disease activity

Abstract: Objective. To determine if measurement of serum complement split products (C4d, Bb, C5b-9) is better than conventional C3 and C4 measurements in distinguishing patients with varying degrees of lupus disease activity, and to determine if the presence of C3d in urine is helpful in distinguishing lupus patients with from those without early lupus nephritis.Methods. Lupus disease activity was prospectively determined at 3 consecutive visits an average of 4 months apart, using the Systemic Lupus Activity Measure (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 31 publications
5
80
0
Order By: Relevance
“…The most widely used assay for assessment of soluble C4d is manufactured by Quidel and has been used in a number of clinical studies regarding vasculitis (Gou et al, 2013), cardiac arrest (Bisschops et al, 2012) (Jenei et al, 2014), graft rejection (Flechner et al, 2010), mixed cryoglobulinemia (Sansonno et al, 2009), Sjögren's syndrome (Sudzius et al, 2014), lupus (Manzi et al, 1996) and lung cancer (Ajona et al, 2013). According to the manufacturer, this ELISA is based on a neoepitope C4d catching antibody and detection is completed by goat polyclonal anti-C4d.…”
Section: Impact Of Temperature Alterations On C4d Detection By This Nmentioning
confidence: 99%
“…The most widely used assay for assessment of soluble C4d is manufactured by Quidel and has been used in a number of clinical studies regarding vasculitis (Gou et al, 2013), cardiac arrest (Bisschops et al, 2012) (Jenei et al, 2014), graft rejection (Flechner et al, 2010), mixed cryoglobulinemia (Sansonno et al, 2009), Sjögren's syndrome (Sudzius et al, 2014), lupus (Manzi et al, 1996) and lung cancer (Ajona et al, 2013). According to the manufacturer, this ELISA is based on a neoepitope C4d catching antibody and detection is completed by goat polyclonal anti-C4d.…”
Section: Impact Of Temperature Alterations On C4d Detection By This Nmentioning
confidence: 99%
“…Though, various studies have shown relationships between complement consumption and SLE disease activity, most have been done in adults [22][23][24]. Studies in children with LN are limited and restricted to the analysis of individual parameters [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Although serum levels of C3, C4, and their activation-derived products are frequently used to monitor disease activity in SLE, their value as biomark-ers is a subject of controversy (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). These observations have led us to consider measurement of complement activation products bound to circulating blood cells (14,15).…”
mentioning
confidence: 99%